Smart triage: Development of a rapid pediatric triage algorithm for use in low-and-middle income countries - Mawji, Alishah; Li, Edmond; Dunsmuir, Dustin; Komugisha, Clare; Novakowski, Stefanie K.; Wiens, Matthew O.; Vesuvius, Tagoola Abner; Kissoon, Niranjan; Ansermino, J. Mark (Frontiers in Pediatrics, 2022)
Introduction Early and accurate recognition of children at risk of progressing to critical illness could contribute to improved patient outcomes and resource allocation. In resource limited settings digital triage tools can support decision making and improve healthcare delivery. We developed a model for rapid identification of critically ill children at triage. Methods This was a prospective cohort study of acutely ill children presenting at Jinja Regional Referral Hospital in Eastern Uganda. Variables collected in the emergency department informed the development of a logistic model based on hospital admission using bootstrap stepwise regression. Low and high-risk thresholds for 90% minimum sensitivity and specificity, respectively generated three risk level categories. Performance was assessed using receiver operating characteristic curve analysis on a held-out test set generated by an 80:20 split with 10-fold cross validation. A risk stratification table informed clinical interpretation. Results The model derivation cohort included 1612 participants, with an admission rate of approximately 23%. The majority of admitted patients were under five years old and presenting with sepsis, malaria, or pneumonia. A 9-predictor triage model was derived: logit (p) = -32·888 + (0·252, age) + (0·016, heart rate) + (0·819, temperature) + (-0·022, mid-upper arm circumference) + (0·048 transformed oxygen saturation) + (1·793, parent concern) + (1·012, difficulty breathing) + (1·814, oedema) + (1·506, pallor). The model afforded good discrimination, calibration, and risk stratification at the selected thresholds of 8% and 40%. Conclusion In a low income, pediatric population, we developed a nine variable triage model with high sensitivity and specificity to predict who should be admitted. The triage model can be integrated into any digital platform and used with minimal training to guide rapid identification of critically ill children at first contact. External validation and clinical implementation are in progress.